Organizational Role Stress among College Teachers in Relation to Gender - Kaur, Supreet; Sachdeva, Ruchi (Gyan Management Journal, 2014)
The modern world, which is said to be a world of achievement, is also a world of stress. One finds, stress everywhere, whether it be within the family, organization or a,zy other social or economic activity. The present study highlights that gender difference exists in an organization. In the modern world where men and women are equal; the women still faces lot of problems in an organization. Women play vital role in the development of the country. They not easily and well in time maintaining their family life but now a days have prominent figure in the society. The study is conducted on 52 college teachers and the result gives female teachers exhibits more organizational role stress as compared to their male counterparts. This is due to the reason that women play dual role in our society. Till today are women bounded in domestic duties instead of working still in a reputed profession. Our culture still has many deficiencies to fill the equality gap between male and female on their counterparts. But, it takes so many times and we must have courage to do this to uplift the position of female members of our society.